Effects of mulberry leaf extract on the intestinal health of spotted sea bass (Lateolabrax maculatus) - Zhou, Sishun; Huang, Zhangfan; Lin, Hao; Kong, Lumin; Ma, Jianrong; Long, Zhongying; Qin, Huihui; Liu, Longhui; Lin, Yi; Li, Zhongbao (Frontiers in Marine Science, 2023)
Mulberry leaf extract (ELM) has the functions of promoting growth, antioxidant, improving intestinal microbial composition, thus providing a potential solution the occurrence of fish intestinal diseases. Therefore, this experiment was conducted to explore the effects of ELM on intestinal health of spotted sea bass Lateolabrax maculatus. A total of 360 spotted sea bass (9.00 ± 0.02 g) were selected and randomly divided into 6 groups. Fish in each group were given feed with varying ELM concentration (0, 3, 6, 9, 12, 15 g/kg) for 52 days, respectively. Results show, dietary intake of 9 g/kg ELM increased the weight gain, specific growth ratio and feed intake of the spotted sea bass (P<0.05). Meanwhile, dietary intake of 9 g/kg ELM increased the activity of enteric trypsin, amylase and lipase (P<0.05). The enteric catalase activity was improved in fish fed with 3 g/kg ELM (P<0.05), while a limited effect of ELM on the activity of enteric superoxide dismutase, glutathione, and content of malonaldehyde was observed (P>0.05). ELM improved the morphology of fish intestine, as manifested in significant improvement in the length of intestinal villi, thereby increasing the surface area of the intestinal tract (P<0.05). Compared with the control group, dietary intake of ELM significantly increased the intestinal microbial ACE, Chao1, and Shannon indexes of fish (P<0.05), indicated that the intestinal microbial composition and the abundance of the dominant flora of fish were improved. The above results suggested that the dietary supplementation of about 9 g/kg ELM can improve the growth performance, enteric antioxidant capacity, and intestinal morphology and microbial composition, therefore improving the intestinal health of spotted sea bass. The research results provide a theoretical basis for the application of ELM in improving the enteric health of spotted sea bass, and providing a potential solution the occurrence of fish intestinal diseases.